Clinical characteristics and factors associated with severe COVID-19 among hospitalized pediatric patients: a retrospective cohort study in the Chaoshan region of China - Wang, Xianyao; Ma, Ruiling; Zhong, Wenshan; Lin, Haipeng; Zhou, Hachao; Xiao, Zhiwei; Lin, Shaofen; Guo, Yutao; Zheng, Xufeng; Lin, Mingxiang (Frontiers in Pediatrics, 2025)
BackgroundSince 2019, COVID-19 has substantially impacted global public health. Although pediatric cases generally manifest with mild symptoms, severe and even fatal outcomes have occurred. Despite the decreased viral transmissibility and pathogenicity observed in the post-pandemic era, identifying early clinical indicators for severe pediatric COVID-19 remains crucial.MethodA retrospective cohort study analyzed 287 hospitalized pediatric COVID-19 patients admitted from December 2022 to August 2023. Clinical and laboratory data were compared between severe/critical and mild/moderate groups using univariable and multivariable analyses.ResultsAmong hospitalized patients, 82.2% were under 3 years, and severe or critical illness occurred in 32.8%. Fatigue (OR = 2.505, 95% CI: 1.359–4.615, P = 0.003) and hoarseness (OR = 2.781, 95% CI: 1.188–6.510, P = 0.018) were independent predictors of severity in multivariable analysis. In univariable analysis, elevated white blood cell counts, neutrophil percentage, procalcitonin (PCT), and reduced bicarbonate (CO₂) levels were also significantly associated with severe disease. All deaths (n = 3) involved children aged 1–1.5 years with acute necrotizing encephalopathy (ANE), two of whom also met diagnostic criteria for multisystem inflammatory syndrome in children (MIS-C).ConclusionPediatric COVID-19 hospitalizations predominantly involved children under 3 years of age. Fatigue was independently associated with severe or critical illness, potentially indicating early neurological involvement. Hoarseness was frequently observed in severe cases. Based on our cohort, particular attention may be warranted for children aged 1–1.5 years presenting with neurological symptoms, as all fatal cases (n = 3) in this age group were associated with acute necrotizing encephalopathy (ANE), and two were additionally complicated by multisystem inflammatory syndrome in children (MIS-C).